Aramejskie rękopisy Księgi Tobita z Qumran (4Q196-200) – historia i egzegeza - Kowalski, Kamil Jan (The Biblical Annals, 2017)
The year 1995 was pivotal for research on the Book of Tobit, when the Aramaic and Hebrew manuscripts of this work found at Qumran were first published. The pres- ent article unfolds the history of the manuscripts’ discovery in 1952 in Qumran Cave 4, then the long process of publishing the recovered texts, and that publication’s effect on the renewal of scholarly interest in the Book of Tobit. The first part describes the Qumran texts’ first publication as well as the significant later works which included the manuscript texts along with their translations. In the next section the author describes the actual condition and contents of the discovered manuscripts. Next he explores the subject of the intertextuality of the book, focusing on Greek and Latin references known before 1952. The fourth section of the article is the presentation of status quaestionis – selected issues regarding the Book of Tobit and how they have been impacted by the discovered texts, 4Q196-200. In particular, it reconsiders the language in which the book was originally written, the compositional integrity of the text, and the matter of origins and the influence of ancient Near Eastern culture (especially of Words of Ahikar) upon the structure and contents of the biblical text. The last part of the article compares the Aramaic fragments with the two known Greek versions of Tobit (both the longer and shorter) and presents the results of this analysis. The purpose of this article is to show the great importance of the finding and publication of the 4Q196-200 manuscripts for advancing research on the biblical book, and to retrace the course of such research on the Book of Tobit, beginning in 1952 until now.